Complete recovery of chronic Osmotic Demyelination Syndrome with plasma exchange - Mahmood, Sumbal Nasir; Mukhtar, Kunwer Naveed; Naveed, Osama Kunwer; Naveed, Ahmed Kunwer (Journal of Clinical Nephrology, 2018)
A 50-years old female presented with dysarthria, inability to swallow and quadriparesis for three weeks. She had rapid correction of her serum sodium (Na) from 99meq/l to 138meq/l within 24 hours 1 week prior to development of these symptoms. She was diagnosed as a case of Osmotic demyelination syndrome (ODS) formerly known as central pontine myelinolysis (CPM) which was confirmed by MRI. She underwent Plasma Exchange (PE) on the 20th day since her symptoms started and underwent 7 cycles of PE with complete neurological recovery. Pt was discharged with ability to ambulate independently and complete recovery of speech and swallowing. Hence, we report that PE is beneficial in chronic ODS.